If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -3 = 37 + -1t Reorder the terms: -3 + 4t = 37 + -1t Solving -3 + 4t = 37 + -1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 't' to each side of the equation. -3 + 4t + t = 37 + -1t + t Combine like terms: 4t + t = 5t -3 + 5t = 37 + -1t + t Combine like terms: -1t + t = 0 -3 + 5t = 37 + 0 -3 + 5t = 37 Add '3' to each side of the equation. -3 + 3 + 5t = 37 + 3 Combine like terms: -3 + 3 = 0 0 + 5t = 37 + 3 5t = 37 + 3 Combine like terms: 37 + 3 = 40 5t = 40 Divide each side by '5'. t = 8 Simplifying t = 8
| 5b-7=-13 | | 5x+22+2x=-48 | | x-7/6=1-x/7 | | 5g+7+3g=31 | | 60a^5-24a^4+36a^3= | | 15z+30=15y+30 | | 6(W+3)=-2(5W-5)+2W | | 3(9+1)-5=(2y-2) | | k-7=10k-16 | | x^3-4x^2+x-9=0 | | 3i+10=14i-12 | | n^2-81= | | 8y+20=16-12 | | 7/2x=-21 | | 6x-5=8x+13 | | e^2x=1/9 | | -54+12x=6(x-3) | | F=1/9k(d-n) | | 6-3/4x=9 | | 6a^2-10=422 | | 3/7=r/4 | | 8(r+3)=72 | | 47=-2-7x | | -1x-52=x^2+6x+6 | | -0.0018x^2+0.06x+1.5=0 | | 3/4x-9=8 | | -3/2x-6 | | 7-5[4-(6y-3)]= | | 9x^4-12x^3+6x^2=0 | | -1/6m=31 | | -4=+15+2 | | 6x^3-14x^2+7x-6=0 |